A ambiguidade do Eu na teoria freudiana: um estudo a partir do conceito de narcisismo - Filla, Munique Gaio (2022)
This study aims to sustain the radical ambiguity of the Ego (Ich) in Freudian theory, taking narcissism as a guiding thread. At the beginning of our journey, we presented Freud's first metapsychological theory and the idea of psychic conflict on which it was based, carried out by the opposition between the Ego and sexuality. Next, we show how the introduction of narcissism affects this disposition of conflict, insofar as it modifies the status of the Ego, which also has a sexual nature, bringing it closer to the opposite pole, the one from which it defended itself. From this, we indicate how narcissism impels the reconfigurations proposed by the psychoanalyst in the field of drive theory and psychic topography, in the “turn” of 1920. Considering that such changes do not solve the problem of the Ego, but bring even more complexity to this psychic instance, we show the border position that it comes to occupy between the Id, the Superego and the external world, in addition to the dubious relationship it establishes with the life drives and the death drives. Once again, starting from narcissism, specifically from its contribution to the notion of desexualization, we emphasize that the Ego does not only serve the life drives and their binding objective, as it happens when it performs the synthesis function that characterizes it. In its identification processes, the Ego transforms object libido into narcissistic libido and abandons its love objects. With this, it desexualizes the libido, weakens the erotic components that maintain the fusion between the life and death drives and causes the defusion of drives, also serving to the unbinding. Finally, we approach the foundations of psychoanalytic treatment, highlighting how the technique moves towards the objective of strengthening the Ego in Freud's writings, in order to finally make explicit an internal tension in his theory. The bet on the Ego in the psychoanalytic clinic is confronted with the internal contradictions that this psychic instance carries, demonstrated throughout the work from the point of view of narcissism.